Semantic Lidar-Inertial SLAM for Dynamic Scenes - Zean Bu; Changku Sun; Peng Wang (Applied Sciences, 2022)
Over the past few years, many impressive lidar-inertial SLAM systems have been developed and perform well under static scenes. However, most tasks are under dynamic environments in real life, and the determination of a method to improve accuracy and robustness poses a challenge. In this paper, we propose a semantic lidar-inertial SLAM approach with the combination of a point cloud semantic segmentation network and lidar-inertial SLAM LIO mapping for dynamic scenes. We import an attention mechanism to the PointConv network to build an attention weight function to improve the capacity to predict details. The semantic segmentation results of the point clouds from lidar enable us to obtain point-wise labels for each lidar frame. After filtering the dynamic objects, the refined global map of the lidar-inertial SLAM sytem is clearer, and the estimated trajectory can achieve a higher precision. We conduct experiments on an UrbanNav dataset, whose challenging highway sequences have a large number of moving cars and pedestrians. The results demonstrate that, compared with other SLAM systems, the accuracy of trajectory can be improved to different degrees.